2022
DOI: 10.1139/bcb-2021-0558
|View full text |Cite
|
Sign up to set email alerts
|

Hoxa5 inhibits adipocyte proliferation through transcriptional regulation of Ccne1 and blocking JAK2/STAT3 signaling pathway in mice

Abstract: The highly regulated proliferation of adipocytes plays a momentous role in fat development and obesity. Hoxa5 is an important member of the Hox family, its encoded protein is an important transcription factor related to development, and its differential expression in different adipose tissues seems to indicate that Hoxa5 may be involved in the regulation of adipocyte proliferation. To evaluate the regulatory mechanism of Hoxa5 on adipocyte proliferation, we constructed a variety of Hoxa5 expression vectors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Only a few studies have focused on adipocytes, but they have revealed the diversified roles of them in fat accumulation. HOXA5 suppresses adipocyte proliferation via the transcriptional regulation of CCNE1 and inhibiting the JAK2/STAT3 signaling pathway [ 37 ]. The epigenetic dysregulation of the HOXA5 gene is associated with adipocyte hypertrophy in human obesity [ 38 ] and contributes to adipose differentiation in mice [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have focused on adipocytes, but they have revealed the diversified roles of them in fat accumulation. HOXA5 suppresses adipocyte proliferation via the transcriptional regulation of CCNE1 and inhibiting the JAK2/STAT3 signaling pathway [ 37 ]. The epigenetic dysregulation of the HOXA5 gene is associated with adipocyte hypertrophy in human obesity [ 38 ] and contributes to adipose differentiation in mice [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some biological processes such as hematopoiesis [ 4 ], vascularization [ 5 ], and fertility [ 6 ] needs the participation of HOX gene family. Function as transcription factors, abnormal activation of HOX genes leads to the dysregulation of downstream signal pathways resulting in the development of various diseases [ 7 ]. Indeed, many HOX genes are considered as key regulators for their implications in gene translocation, gene mutation, or improper gene expression in tumor, which play a critical role in the proliferation, invasion, and metastasis stages of tumor [ 8 ].…”
Section: Introductionmentioning
confidence: 99%